(untitled) (CIPEEX, 2022)
INTRODUCTION: THE SYNDROME OF HYPERTENSIVE SPECIFIC OF THE GESTATION (SHEG) IS A DISEASE OF GREAT MORBIDITY AND MORTALITY IN PREGNANCY, BECOMING ONE OF THE HYPERTENSIVE€™S SYNDROMES. SPECIAL ATTENTION SHOULD BE GIVEN TO PREECLAMPSIA THAT OCCURS AS A FORM (ALONE OR ASSOCIATED) OF CHRONIC ARTERIAL HYPERTENSION, SINCE IT IS LINKED TO MATERNAL AND PERINATAL OUTCOMES. IT IS IMPORTANT FOR THE HEALTH TEAM TO IDENTIFY THE PREDISPOSING FACTORS FOR THIS PATHOLOGY IN ORDER TO RECOGNIZE THE DEVELOPING OF THE DISEASE ANY TIME DURING THE PRE-NATAL PERIOD (PN). IT HELPS TO THE PREVENTION, PROMOTION AND PROTECTION OF HEALTH OF THE BINOMIAL PREGNANT-FETUS. OBJECTIVE: THE PURPOSE OF THIS STUDY AIMS TO DESCRIBE THE NURSING PROCEDURES IN THE PREGNANT WOMEN CARE DETECTED WITH SHEG. METHODOLOGY: THE METHODOLOGICAL ASSETS USED WAS THE INTEGRATIVE LITERATURE REVIEW OF ARTICLES PUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL) AND AVAILABLE IN FULL TEXT IN THE DATABASES: LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS) AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND NURSING DATABASE (BDENF), IN THE PERIOD BETWEEN 2010-2016, IN THE PORTUGUESE LANGUAGE. THE ANALYSIS OF DATA THEFOLLOWS THE RECOMMENDATIONS OF MENDES ET AL. (2008), WHICH PROPOSES HIS PROCESSUS FOR THE ELABORATION OF AN INTEGRATIVE LITERATURE REVIEW. &NBSP;RESULTS: TWELVE ARTICLES WERE INCLUDED IN THE HARD CORE OF THE ANALYSIS OF THIS RESEARCH. FOR THIS, TWO CATEGORIES HAVE EMERGED: 1) THE CONCEPTUALIZATION, THE INCIDENCE OF RISK FACTORS, AND THE EMERGING OF SIGNS AND SYMPTOMS OF SHEG; AND 2) THE NURSING CARE OF SHEG. THE SYSTEMATIZATION OF NURSING CARE FOR THIS TYPE OF PATIENT WAS A CHALLENGE CONSIDERING THE NECESSITY OF PROVIDING ASSISTANCE TO THE PATIENTS’ SELF-CARE DEMANDS PROMOTING AN EMANCIPATORY ASSISTANCE FOR THE GENERAL WELFARE OF THE BINOMIAL MOTHER-FETUS. &NBSP;CONCLUSION: THE INCIDENCE OF SHEG IN PREGNANT WOMEN, AS SO FAR IT IS DETECTED, REQUIRES THAT THE HEALTH PROFESSIONAL TEAM IS ABLE TO BE PREPARED TAKING PREVENTIVE ACTIONS LEADING TO THE PREVENTION OF THE MATERNAL-FETAL BINOMIAL. THIS ARTICLE HAS CONFIRMED THE HYPOTHESES THAT NURSES HAVE TECHNICAL AND SCIENTIFIC KNOWLEDGE TO RECOGNIZE THE SIGNS OF SHEG AS ALSO TO STARTTHE PREVENT PROGNOSIS AS SOON IT IS DETECTED